Aspect Ratio Plays a Role in the Hazard Potential of CeO(2) Nanoparticles in Mouse Lung and Zebrafish Gastrointestinal Tract - Lin, Sijie (2014)
We have previously demonstrated that there is a relationship between the aspect ratio (AR) of CeO(2) nanoparticles and in vitro hazard potential. CeO(2) nanorods with AR ≥ 22 induced lysosomal damage and progressive effects on IL-1β production and cytotoxicity in the human myeloid cell line, THP-1. In order to determine whether this toxicological paradigm for long aspect ratio (LAR) CeO(2) is also relevant in vivo, we performed comparative studies in the mouse lung and gastrointestinal tract (GIT) of zebrafish larvae. Although oropharyngeal aspiration could induce acute lung inflammation for CeO(2) nanospheres and nanorods, only the nanorods with the highest AR (C5) induced significant IL-1β and TGF-β1 production in the bronchoalveolar lavage fluid (BALF) at 21 days but not inducing pulmonary fibrosis. However, after a longer duration (44 days) exposure to 4 mg/kg of the C5 nanorods, more collagen production was seen with CeO(2) nanorods vs. nanospheres after correcting for Ce lung burden. Using an oral-exposure model in zebrafish larvae, we demonstrated that C5 nanorods also induced significant growth inhibition, a decrease in body weight, and delayed vertebral calcification. In contrast, CeO(2) nanospheres and shorter nanorods had no effect. Histological and transmission electron microscopy (TEM) analyses showed that the key injury mechanism of C5 was in the epithelial lining of the GIT, which demonstrated blunted microvilli and compromised digestive function. All considered, these data demonstrate that, similar to cellular studies, LAR CeO(2) nanorods exhibit more toxicity in the lung and GIT, which could be relevant to inhalation and environmental hazard potential.